Ultra-high pressure improved gelation and digestive properties of Tai Lake whitebait myofibrillar protein - Mingfeng Xu; Xiangxiang Ni; Qiwei Liu; Chengcheng Chen; Xiaohong Deng; Xiu Wang; Rongrong Yu (Food Chemistry: X, 2024)
This study investigated the effects of ultra-high pressure (UHP) at different levels on the physicochemical properties, gelling properties, and in vitro digestion characteristics of myofibrillar protein (MP) in Tai Lake whitebait. The α-helix gradually unfolded and transformed into β-sheet as the pressure increased from 0 to 400 MPa. In addition, the elastic modulus (G') and viscous modulus (G'') of the 400 MPa-treated MP samples increased by 4.8 and 3.8 times, respectively, compared with the control group. The gel properties of the MP also increased significantly after UHP treatment, e.g., the gel strength increased by a 4.8-fold when the pressure reached 400 Mpa, compared with the control group. The results of in vitro simulated digestion showed that the 400 MPa-treated MP gel samples showed a 1.8-fold increase in digestibility and a 69.6 % decrease in digestible particle size compared with the control group.